Risk factors for Echinococcus coproantigen positivity in dogs from the Alay valley, Kyrgyzstan. Issue 6 (7th October 2015) - Mastin, A.; van Kesteren, F.; Torgerson, P.R.; Ziadinov, I.; Mytynova, B.; Rogan, M.T.; Tursunov, T.; Craig, P.S.
Abstract Echinococcosis, caused by the zoonotic cestodes Echinococcus granulosus (sensu lato) and Echinococcus multilocularis, is highly endemic in the Central Asian Republic of Kyrgyzstan, and is being identified increasingly as a public health problem, especially amongst pastoral communities. As domestic dogs are considered to be the main source of human infection, the identification of potential transmission pathways is of relevance when considering implementing an echinococcosis control scheme. The current report describes the results of an analytical study of canine Echinococcus coproantigen enzyme-linked immunosorbent assay (ELISA) prevalence in the Alay valley of southern Kyrgyzstan prior to the commencement of regular praziquantel dosing of dogs. A logistic regression model using a form of Bayes modal estimation was used to identify possible risk factors for coproantigen positivity, and the output was interpreted in a Bayesian context (posterior distributions of the coefficients of interest). The study found that sheepdogs had lower odds of coproantigen positivity, as did dogs in households with donkeys, where owners had knowledge of echinococcosis, and households which engaged in home slaughtering. Surprisingly, there was no evidence of an association between free roaming or previous praziquantel dosing and coproantigen positivity, as has been found in previous studies. Possible reasons for these findings are discussed in the context of the epidemiology of echinococcosis and potential intervention approaches.